2001
DOI: 10.1159/000047145
|View full text |Cite
|
Sign up to set email alerts
|

Expression and Activity of the Ca<sup>2+</sup>-ATPase Enzyme in Human Neonatal Erythrocytes

Abstract: The plasma membrane Ca2+-ATPase (PMCA) is one of the main regulators of Ca2+ homeostasis. We studied the perinatal alteration of the abundance and the activity of PMCA molecules in human erythrocytes in pre-term and full-term neonates and children at the age of 1–4 years. The lower abundance of the 4b isoform was associated with lower enzyme activity in full-term neonates compared to children. Although the number of PMCA molecules was higher in pre-term neonates, their total PMCA activiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 24 publications
2
2
0
Order By: Relevance
“…Our data demonstrated that while the main isoform appears to be PMCA4, the PMCA1 isoform is also represented in the erythrocyte ghosts. It extends the results obtained by Kocsis et al [24] , which using the PMCA4b-specific antibody showed this protein as an exclusive in erythrocytes of preterm newborn. In the control group, the PMCA1 amount was higher at birth and decreased slightly after 24 h, reaching the same level as the Mg-treated one.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Our data demonstrated that while the main isoform appears to be PMCA4, the PMCA1 isoform is also represented in the erythrocyte ghosts. It extends the results obtained by Kocsis et al [24] , which using the PMCA4b-specific antibody showed this protein as an exclusive in erythrocytes of preterm newborn. In the control group, the PMCA1 amount was higher at birth and decreased slightly after 24 h, reaching the same level as the Mg-treated one.…”
Section: Discussionsupporting
confidence: 90%
“…After 24 h, the total amount of PMCA in control erythrocyte ghosts declined, but increased both basal and CaM-stimulated activity. These results could confirm that some of the enzyme molecules in preterm controls may exist in an inactive form, as suggested by others [24] . In contrary, at the same time in the Mg-treated group the higher amount of PMCA correlated with the augmented activity of the enzyme.…”
Section: Discussionsupporting
confidence: 88%
“…In contrast, in hippocampal neurons, all major Ca 2ϩ extrusion systems are strongly upregulated during the first 2 wk of postnatal development as a consequence of changes in the expression and cellular localization of different isoforms of Ca 2ϩ pumps and exchangers (18). Human neonatal erythrocytes have fewer PMCA molecules, which also exhibit reduced PMCA activity compared with children erythrocytes, indicating that postnatal PMCA undergo developmental changes postnatally (22).…”
Section: Discussionmentioning
confidence: 97%
“…Human erythrocyte PMCA is composed primarily of PMCA4, with PMCA1 expression also having been identified (188,352). PMCA activity declines as red blood cells age in line with increasing glycated hemoglobin, which may make them prone to Ca 2ϩ overload and earmark them for clearance (207).…”
Section: Pmca In Erythrocytesmentioning
confidence: 99%